Magnetic stack structure, magnetic storage device, and method for operating a magnetic storage device

By using Hasler compound and MnN seed layer with high energy barriers in magnetic random access memory devices, a magnetic stacking structure with perpendicular magnetic anisotropy is solved, and the problem of insufficient energy barrier of the magnetic tunnel junction free layer is solved. Improves the storage stability and switching performance of memory devices.

CN109713117BActive Publication Date: 2024-12-13INTERNATIONAL BUSINESS MACHINE CORPORATION +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN201811247710.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2017-10-26
Filing Date
2018-10-25
Publication Date
2024-12-13
Estimated Expiration
2038-10-25

AI Technical Summary

Technical Problem

In the existing magnetic random access memory devices, the free layer of the magnetic tunnel junction is prone to insufficient energy barrier due to thermal fluctuations, which affects the storage stability and switching performance.

Method used

The Hasler compound with a high energy barrier is used as the magnetic layer, and the vertical orientation growth of the Hasler compound is promoted by growing the MnN seed layer on the substrate to form a magnetic stack structure with perpendicular magnetic anisotropy. Used to build magnetic tunnel junctions to improve the performance of memory devices.

Benefits of technology

It realizes efficient data storage and reading in MRAM devices, reduces the demagnetization field, ensures the high perpendicular magnetic anisotropy and stable magnetization direction of the Hasler layer, and improves the performance and reliability of the memory device.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN109713117B_ABST
    Figure CN109713117B_ABST
Patent Text Reader

Abstract

A magnetic stack structure, a magnetic memory device, and a method for operating a magnetic memory device are provided, and a material used as a seed layer in the formation of an MRAM element is disclosed. Specifically, a MnN layer oriented in a (001) direction is grown on a substrate. A magnetic layer covering and contacting the MnN layer forms a partial magnetic tunnel junction, wherein the magnetic layer includes a Hasler compound containing Mn. The magnetic tunnel junction includes the magnetic layer, a tunnel barrier covering the magnetic layer, and a first (magnetic) electrode covering the tunnel barrier. A second electrode contacts the MnN layer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a magnetic tunnel junction magnetoresistive device, and more particularly to a magnetic random access memory using the device. Background Art

[0002] Magnetic random access memory (MRAM) devices use magnetic tunnel junctions (MTJs) as storage elements, where the MTJ consists of at least two magnetic electrodes separated by a tunnel barrier. One of the magnetic electrodes has a magnetic moment with a fixed direction, and the other of the magnetic electrodes (called a free layer or storage layer) has a magnetic moment with a direction parallel or antiparallel to the direction of the fixed magnetic moment, so that the MTJ has two different states. The two states of the MTJ have significantly different resistance values ​​for spin-polarized tunneling currents. When the MTJ element is placed between two wires or electrodes, current can pass between the electrodes to read the resistance state and / or write (change) the state of the MTJ using spin transfer torque. The area of ​​the MTJ can be customized to match the corresponding technology node of the existing CMOS technology. As the area is reduced, the energy barrier for the free layer to rotate relative to the fixed layer due to thermal fluctuations is reduced. This can be problematic if the magnetic electrodes are made of materials with insufficiently high energy barriers. Summary of the invention

[0003] New materials with high energy barriers are disclosed for use in MRAM devices. High anisotropy energy can be achieved by materials with intrinsic magnetic crystal anisotropy, such as the Heusler compounds disclosed herein, because their energy barriers are directly related to the magnetic anisotropy of the free layer.

[0004] Heusler compounds have the chemical formula X 2 YZ or X'X"YZ, where X, X', X" and Y are transition metals or lanthanides (rare earth metals) and Z is a main group metal. Depending on the exchange interaction between the magnetic moments at X, X', X" and / or Y, the Heusler compounds disclosed herein are ferromagnetic or ferrimagnetic. In addition, while most Heusler compounds are cubic and exhibit weak or insignificant magnetic anisotropy, some Heusler compounds are tetragonally deformed: due to this deformation, the magnetization exhibited by these compounds can be aligned along the tetragonal axis. Therefore, due to the magnetocrystalline anisotropy associated with the tetragonal deformed structure, a film formed from such material can exhibit perpendicular magnetic anisotropy (PMA). Some examples of such tetragonal Heusler compounds suitable for use herein are binary compounds (e.g., Mn 3 Z, where Z = Ge, Ga, Sn or Sb) and ternary compounds (such as Mn 2 CuSb、Mn 2 CoSn、Mn 2 OsSn, etc.).

[0005] Figure 1 Shows the desired material stack, where the Heusler alloy is used as a hard magnet with large perpendicular magnetic anisotropy. This material stack can be used in a variety of applications: as a storage layer in a disk drive, as a fixed layer in a magnetic tunnel junction, and as an alternative to hard magnets (thus avoiding the use of rare earth elements). For MRAM applications, the thickness of the Heusler alloy should be very thin so that (i) it can be switched by spin-transfer torque and (ii) the demagnetizing field is minimized. Therefore, the Heusler compound is grown on a lower layer to provide electrical connection. These lower layers are also used to promote the growth of the Heusler layer to maintain the appropriate crystal orientation for high perpendicular magnetic anisotropy (PMA), where the magnetization of the Heusler layer is perpendicular to the plane of the layer. Heusler compounds with significant PMA typically exhibit tetragonal distortion from their cubic structure; thus, the Heusler layer is grown such that the tetragonal axis is perpendicular to the layer. The Heusler compounds disclosed herein are preferably formed from binary or ternary alloys containing manganese.

[0006] Disclosed herein is a seed layer that promotes the growth of an oriented Heusler compound to provide the desired crystal orientation with respect to the tetragonal axis (i.e., the c-axis) perpendicular to the growth plane. The seed layer contains light elements, and MnN is a preferred candidate because nitrogen is also a light element. In addition, MnN has a simple cubic structure with a lattice constant of 4.01 Å, which highly matches the lattice constant of the Mn-based tetragonal Heusler compound.

[0007] One embodiment of the present invention is a magnetic stack structure that includes a substrate and an MnN layer covering the substrate, where the MnN layer is mainly oriented in the (001) direction. A magnetic layer covers and contacts the MnN layer. The magnetic layer (which is ferromagnetic or antiferromagnetic) forms part of a magnetic tunnel junction; in addition, the magnetic layer includes an Mn-containing Heusler compound.

[0008] In a preferred embodiment, the magnetic tunnel junction includes the magnetic layer, a tunnel barrier (such as MgO, AlN, or Mg 1-x Al 2-x O 4 , where -0.5 < x < 0.5), and a first (magnetic) electrode covering the tunnel barrier. A second electrode contacts the MnN layer, allowing current to pass through the magnetic stack structure. The MnN layer, the magnetic layer, and the magnetic tunnel junction can advantageously have corresponding crystal structures that are consistent with each other. At least 100 such magnetic stack structures can be interconnected to form a storage device into which data can be read or from which data can be read out.

[0009] Another embodiment of the present invention is a magnetic stack structure comprising a substrate and a MnN layer covering the substrate. The MnN layer is mainly oriented in the (001) direction, and the magnetic layer covers and contacts the MnN layer. The magnetic layer comprises a Heusler compound containing Mn, and the magnetic layer is ferromagnetic or ferrimagnetic. The magnetic layer can advantageously include discrete magnetic domains. When data is stored in these magnetic domains, they have corresponding magnetization directions corresponding to these data. BRIEF DESCRIPTION OF THE DRAWINGS

[0010] Figure 1 Schematic diagram of a Heusler-based hard magnet with giant perpendicular magnetic anisotropy (PMA).

[0011] Figure 2 The results show that the sputtering gas has different ratios of Ar:N. 2 As-grown MnN film, Mn:N ratio determined by Rutherford backscattering (RBS).

[0012] Figure 3 Shows the The MnN deposition rate of the thick MnN film depends on the N content of the sputtering gas. 2 Dependence on content.

[0013] Figure 4 shows the effect of Si(100) / SiO 2 On the substrate Grown on the MnN seed layer Cr film (second to last) and Ir 3 Out-of-plane X-ray diffraction θ-2θ scan of the film (second from the positive). For comparison, the X-ray diffraction on Si(100) / SiO 2 Directly grown on substrate without MnN seed layer Cr film (bottom trace) and Ir 3 X-ray diffraction (XRD) scan of the film (top trace).

[0014] Figure 5 Shows the Grown on a thick nitride seed layer Thick Mn 3 X-ray diffraction θ-2θ scan of Sn Heusler compound. The nitride seed layer is directly deposited on amorphous SiO at room temperature. 2 On, Mn 3 The Sn film was deposited at a substrate temperature of 200°C.

[0015] Figure 6Includes left and right images. Figure 6 The left figure shows the Figure 5 MnN / Mn 3 Corresponding cross-sectional high-resolution transmission electron microscopy (HR-TEM) image of the Sn sample. Figure 6 The right picture is Figure 6 Magnified view of the boxed area in the left figure. Figure 6 The dashed line in the right image roughly marks the interface between the two layers.

[0016] Figure 7 Shows the measured at room temperature Figure 5 Mn 3 Hysteresis loop of magnetization of Sn Heusler compound relative to perpendicular magnetic field.

[0017] Fig. 8A shows the out-of-plane X-ray diffraction θ-2θ scan, Figure 8B The results show that the MgO(001) substrates deposited at room temperature Atomic force microscopy scan of MnN film. Fig. 8A The inset in the figure is a magnified image scanning around the diffraction peaks of MnN (002) and MgO (002). Figure 8B Measured RMS roughness r rms for

[0018] Fig. 9 A magnetic tunnel junction device comprising a MnN seed layer and a Heusler layer as described herein is shown.

[0019] Fig.10 Shows the contents Fig. 9 Some layers of the racetrack device are shown. DETAILED DESCRIPTION

[0020] MnN film has a 1×10 -9 The 25 nm thick, thermally oxidized SiO 2 The Si substrate was sequentially cleaned in a UV ozone chamber to remove any adsorbed organic material, rinsed in a deionized water bath to remove water-soluble contaminants and particles, exposed to hot isopropyl alcohol (IPA) vapor to remove water, and finally dried in a hot nitrogen oven at ~60°C. The MnN seed layer was deposited on a 3×10 -3 The relative ratio of Mn:N in the MnN layer is adjusted by adjusting the Ar:N 2 To control, such as Figure 2 The composition of the MnN film was determined by Rutherford backscattering (RBS) from a MnN film that had been deposited on a graphite substrate and A series of Pt coatings to prevent oxidation when exposed to the ambient environment MnN film determination. The graphite substrate (which contains mainly carbon - an element with a lower atomic number than nitrogen) allows the nitrogen content of the MnN film to be determined to within + / - 0.5%. The stoichiometric film of MnN is 20:80 Ar:N 2 Alternatively, MnN can be grown by sputtering from a MnN target.

[0021] The conductivity of these MnN films was determined close to the center of the sample by a 4-point in-line probe technique. The spacing between the 4 contacts was ~1 mm, which is much smaller than the sample size (1 inch diameter). The conductivity of the MnN film increases as the N content in the film decreases. The conductivity of the stoichiometric MnN film (approximately 2.65 MS / m) is comparable to the metallic underlayers commonly used in magnetic tunnel junction stacks (e.g., the conductivity of Ti is 2.38 MS / m; the conductivity of Ta is 1.05 MS / m). Moreover, the conductivity of the MnN film is almost an order of magnitude higher than the TaN seed layer also used in MTJ stacks (e.g., by reactive RF magnetron sputtering in argon with 10% N 2 The conductivity of the grown TaN film is reported to be 0.14 MS / m). This significantly higher conductivity of MnN compared to that of TaN facilitates the use of thicker MnN films of tens of nm within the MTJ stack. The deposition rate of the MnN film depends on the N content in the sputtering gas mixture. 2 Content, with N 2 The content of Figure 3 ). For TaN film in N 2 This almost linear reduction in the deposition rate of nitride films has also been observed for growth by reactive RF magnetron sputtering from a Ta metal target in a H:Ar gas mixture (see Nie et al., Applied Physics A, 73, 229 (2001)).

[0022] Figure 4 This indicates that the use of a MnN seed layer promotes a preferred (001) texture in the films deposited thereon. 3 X-ray diffraction (XRD) data of the Cr film and the Cr film, as both have been used as seed layers for the (001)-oriented growth of tetragonal Heusler alloy films. These samples were The ions were covered with a Ta layer to prevent them from oxidation when exposed to the ambient environment. XRD measurements were performed on a Bruker X-ray diffractometer with a General Area Detector Diffraction System (GADDS) area detector. IrMn 3The Cr films were deposited at room temperature on thermally grown Thick amorphous SiO 2 Layer Si(100) substrate (Si(100) / SiO 2 ). These samples were Ta coverage to protect IrMn 3 The layer and the Cr layer were protected from oxidation by exposure to the ambient environment. Only the sample with the Cr layer was annealed (in-situ annealing at 400°C for 30 minutes in the deposition chamber). 3 Film on Si(100) / SiO 2 The BCC Cr film has a mixed texture with (110) and (001) orientations along the normal of the sample. (Preferably and or MnN films with a film thickness in the range of 1000 to 2000 still promote the growth of highly textured films with (001) orientation of both body-centered cubic and face-centered cubic metals or alloys (such as in Figure 4 When using MnN layer, as seen by the presence of the (002) peak and the disappearance of the (111) and (110) peaks).

[0023] Table 1 is a summary of some metallic transition metal nitrides or semiconductor transition metal nitrides. In addition, the lattice constants of these nitrides are relatively close to the lattice constant of cubic MgO ( ), raising the possibility that these nitrides promote the growth of a (001)-oriented MgO tunnel barrier, which is the preferred tunnel barrier for MRAM.

[0024] Table 1 Lattice constants of some metallic nitride layers / semiconductor nitride layers

[0025]

[0026] Figure 5 This indicates that MnN acts as a seed layer to promote the (001) oriented Mn 3 The uniqueness of Sn Heusler film growth. Alternatively, Mn 3 Sn can be made from other Mn 3 Z Heusler alloy instead, where Z = Ge, Ga or Sb. Figure 5 The results from the comparison of Si(100) / SiO 2 / XN (where X = Mn, Ti, V or Ta) / Mn 3 Sn / XRD data along the out-of-plane direction of a series of samples of Ta structure. The nitride layer and Ta cap layer were deposited at room temperature. 3 The Sn layer was deposited at 200 °C. These data reveal that the MnN film is highly textured and has a (001) orientation. This in turn promotes the Mn with a (001) orientation. 3 The growth of Sn Heusler film corresponds to the tetragonal axis (i.e., c-axis) of the film. 3 The magnetization of Sn Heusler film is aligned along its tetragonal axis, so Mn with (001) orientation 3 Sn Heusler films show satisfactory perpendicular magnetic anisotropy (PMA). Because none of TiN, VN and TaN grow on Si(100) / (001) texture, SiO 2 substrate, so these nitrides cannot promote the Mn with the preferred (001) texture 3 Growth of Sn Heusler films.

[0027] Figure 6 Including from Si(100) / SiO 2 / MnN / Mn 3 Sn / Representative cross-sectional high-resolution transmission electron microscopy (HR-TEM) image of a Ta sample. (The topmost part of the Ta is oxidized to form TaO 2 . ) Nitride and Ta capping layers were deposited at room temperature, Mn 3 The Sn layer was deposited at 200°C. The individual layers are labeled in the image; XRD data ( Figure 5 ) shows that the MnN film is highly textured. 3 A magnified view of the interface between Sn Heusler layers showing the overlying Mn 3 The Sn layer is epitaxially grown on the MnN layer.

[0028] Figure 7 Summarizes the collection Figure 5 The same Mn used in the XRD data described in 3 Magnetization data of Sn Heusler films. The hysteresis loops were measured in an out-of-plane geometry at room temperature in a Quantum Design SQUID-VSM (superconducting quantum interference device-vibrating sample magnetometer). These data are consistent with our structural measurements and show that Mn 3Sn Heusler films have their tetragonal axes along the sample normal only when deposited on a MnN seed layer. Mn on other nitrides such as TiN, VN, and TaN 3 Sn Heusler film does not show perpendicular magnetic anisotropy. 3 Sn Heusler films have a large PMA at ambient temperature with a high coercive field of ~2T.

[0029] Fig. 8A and 8B This shows the effectiveness of MnN as a metallic seed layer on a single crystal MgO (001) substrate. 3 The growth of Z (where Z = Ge, Ga, Sn or Sb) Heusler films is particularly relevant. A MnN seed layer is preferred over a conventional Cr seed layer because the seed layer is bonded to the Mn during any subsequent annealing of the Heusler film. 3 The mutual diffusion between Heusler films does not deteriorate the magnetic properties of the Heusler films. Fig. 8A The results show that the Out-of-plane XRD scan of MnN. The Mn film was deposited at room temperature and The MnN film is epitaxially grown on the MgO substrate and the presence of Kiessig fringes indicates high film quality. The periodicity of the fringes is consistent with the thickness of the MnN film. The root mean square roughness (r rms ) indicates that the film is ultra-smooth (see Figure 8B ).

[0030] The structures described herein are suitable for use in a variety of applications, including MRAM elements and racetrack memory devices, such as those described in US Pat. No. 6,834,005, issued Dec. 21, 2004, entitled "Shiftable Magnetic Shift Register and Method of Using the Same," which is incorporated herein. Fig. 9 One such MRAM element is shown in FIG, and arrays thereof can be integrated together to form an MRAM device. As is common with MRAM elements, the tunnel barrier is located between two magnetic electrodes, one of which has a fixed magnetic moment and the other of which has a switchable magnetic moment, thereby allowing data to be recorded and erased. However, unlike prior art MRAM elements, Fig. 9 The first magnetic layer (pinned layer) having a fixed magnetic moment includes a Heusler film, such as the Heusler film described herein. Alternatively, these Heusler films can be ternary compounds, such as Mn 2 CuSb、Mn 2 CoSn、Mn 2 OsSn、Co 2FeGe, etc., or even quaternary compounds such as Co 2 FeGa 0.5 Ge 0.5 An optional (second) pinning layer may be advantageous for better performance and may include Fe, CoFe alloys or materials such as Co 2 MnSi or Co 2 Heusler compound of FeAl.

[0031] Note that Fig. 9 In the present invention, a pinned layer (Heusler layer, which can be ferromagnetic or ferrimagnetic) is overlaid on a MnN seed layer, which in turn is overlaid on a substrate. As described herein, the MnN seed layer and substrate can be advantageously selected to promote the growth of a Heusler layer whose magnetic moment is aligned perpendicular to the plane of the layer. The tunnel barrier is preferably MgO (001), but other (001) oriented tunnel barriers such as CaO and LiF can also be used. Alternatively, MgAl 2 O 4 Can be used as such a tunnel barrier: its lattice spacing can be adjusted by controlling the Mg-Al composition, resulting in a better lattice match with the Heusler compound. The magnetic electrode covering the tunnel barrier may include, for example, Fe, CoFe alloy or CoFeB alloy. The cap layer covering and contacting the magnetic electrode may include Mo, W, Ta, Ru or a combination thereof. Current can be induced by applying a voltage between two magnetic electrodes separated by the tunnel barrier.

[0032] Some of the structures described here can also be used in racetrack memory devices. In this case, the racetrack is a nanowire that can include a substrate, an optional seed layer, an MnN layer, and a first magnetic layer of a Heusler compound. (For possible compositions of these layers, see above for Fig. 9 Note that in the track storage device (see Fig.10 )middle, Fig. 9 The tunnel barrier and switchable magnetic layer shown would not normally be present; however, in this case, Fig. 9 The first magnetic layer shown would have a switchable rather than fixed magnetic moment.) The magnetic domain walls can be moved along the racetrack, as described in U.S. Patent 6,834,005. Data can be read from (and stored in) the racetrack by interrogating (or changing) the orientation of the magnetic moment of the magnetic material between adjacent domain walls within the racetrack.

[0033] The layers described herein may be deposited by any one or more of a number of methods, including magnetron sputtering, electrodeposition, ion beam sputtering, atomic layer deposition, chemical vapor deposition, and thermal evaporation.

[0034] The present invention may be implemented in other specific forms without departing from its spirit or essential features. The described embodiments will be considered in all respects to be merely illustrative and not restrictive. Therefore, the scope of the present invention is indicated by the appended claims rather than the preceding description. All changes within the meaning and equivalent scope of the claims will be included within the scope.

[0035] This application claims priority to and the benefit of U.S. Non-Provisional Patent Application No. 15 / 795,096, filed on October 26, 2017, the contents of which are incorporated herein by reference in their entirety.

Claims

1. A magnetic stacking structure, include: substrate; a MnN layer covering the substrate, wherein the MnN layer is mainly oriented in the (001) direction; as well as A magnetic layer overlying and contacting the MnN layer, the magnetic layer forming part of a magnetic tunnel junction, wherein the magnetic layer comprises a Heusler compound containing Mn, and wherein the magnetic layer is ferromagnetic or ferrimagnetic. 2 . The magnetic stack structure according to claim 1 , wherein the Heusler compound is tetragonal. 3 . The magnetic stack structure of claim 1 , wherein the magnetic layer and the magnetic tunnel junction have respective crystal structures that coincide with each other. 4 . The magnetic stack structure of claim 1 , wherein the MnN layer and the magnetic layer have respective crystal structures that coincide with each other.

5. The magnetic stack structure according to claim 1, wherein the magnetic tunnel junction include: the magnetic layer; a tunnel barrier covering the magnetic layer; as well as A first electrode covers the tunnel barrier, wherein the first electrode is magnetic.

6. The magnetic stack structure according to claim 5, include: A capping layer covers and contacts the first electrode. The magnetic stack structure according to claim 6 , wherein the tunnel barrier is MgO.

8. The magnetic stack structure according to claim 6, wherein the tunnel barrier is Mg 1-x Al 2-x O 4 , where -0.5 <x<0.5。 9 . The magnetic stack structure of claim 6 , wherein the tunnel barrier is AlN.

10. The magnetic stack structure according to claim 6, include: A second electrode contacts the MnN layer.

11. A magnetic storage device, include: At least 100 magnetic stack structures as set forth in claim 10 are interconnected to form a memory device.

12. A method of operating a magnetic storage device, include: Data is written to the first electrode of the magnetic memory device according to claim 11.

13. The method according to claim 12, include: Data stored in the first electrode of the magnetic memory device is read.

14. A magnetic stack structure, include: substrate; a MnN layer covering the substrate, wherein the MnN layer is mainly oriented in the (001) direction; as well as A magnetic layer overlying and contacting the MnN layer, wherein the magnetic layer comprises a Heusler compound containing Mn, and wherein the magnetic layer is ferromagnetic or ferrimagnetic.

15. The magnetic stack structure of claim 14, wherein the magnetic layer comprises discrete magnetic domains. 16 . The magnetic stack structure of claim 15 , wherein the magnetic domains have respective magnetization directions corresponding to data stored in the magnetic stack structure.

Citation Information

Patent Citations

  • Shiftable magnetic shift register and method of using the same

    US6834005B1

  • Magnetoresistive effect element and manufacturing method thereof

    US20140077319A1

  • Termination layer-compensated tunneling magnetoresistance in ferrimagnetic heusler compounds with high perpendicular magnetic anisotropy

    US20170125045A1